2000
DOI: 10.2741/a567
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylesterases moonlight in the male reproductive tract a functional shift pivotal for male fertility

Abstract: This essay addresses the carboxylesterase redundancy in the male reproductive tract seemingly conserved across phyla. Evidence is provided which suggests that carboxylesterases are recruited by the male reproductive system in certain animal groups. These provide advantageous metabolic capabilities to sperm protection, sperm maturation, and sperm use. Rather than an archival record of the available data, we seek possible answers to the central question: Why is carboxylesterase over-expression adaptive with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…We also found that four annotated fecundity‐related genes, PK , StKR‐associated protein , Car and a Sox gene, regulate female fecundity in Ni. lugens (Figs , although these genes have been reported to be associated with male fertility in other species (Mikhailov & Torrado, ; Wen et al ., ; Danshina et al ., ; Wei et al ., ; Jiang et al ., ). In addition, we provide evidence that four genes, Rpg , integrin beta‐PS , RGEF and MPP , are involved in the insect reproduction process (Figs ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that four annotated fecundity‐related genes, PK , StKR‐associated protein , Car and a Sox gene, regulate female fecundity in Ni. lugens (Figs , although these genes have been reported to be associated with male fertility in other species (Mikhailov & Torrado, ; Wen et al ., ; Danshina et al ., ; Wei et al ., ; Jiang et al ., ). In addition, we provide evidence that four genes, Rpg , integrin beta‐PS , RGEF and MPP , are involved in the insect reproduction process (Figs ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has found a direct link between carboxylesterase, the protein involved in malathion‐resistant T. castaneum , and male reproductive function in other invertebrate taxa (Mikhailov and Torrado 2000). The biochemical difference between resistant and susceptible genotypes in T. castaneum involves a significant 44‐fold increase in the activity of carboxylesterase enzyme which confers resistance to malathion (Haubruge et al .…”
Section: Discussionmentioning
confidence: 99%
“…Allele differences in T. castaneum at a single locus generate this difference in esterase activity, which leads to the significant phenotypic effect of malathion‐specific resistance under insecticide stress. In addition to toxin metabolism, the carboxylesterase group is also recognized to play an important role in male reproductive function, specifically differentiation, maturation and emission of spermatozoa (Mikhailov and Torrado 1999, 2000). Research suggests that such carboxylesterases are concentrated as seminal proteins in the male reproductive system of different animal groups (molluscs, Drosophila and rodents) and that these proteins confer improved metabolic capabilities and functions on spermatozoa (Mikhailov and Torrado 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon indicates male sex-associated functions of these enzymes. It was proposed that male genital tract carboxylesterases might protect the male reproductive system against xenobiotic influences, and provide advantageous metabolic capabilities to sperm protection, maturation, and sperm use [2,3].…”
Section: Introductionmentioning
confidence: 99%